MOBILITAS TENAGA KERJA INDONESIA KE LUAR NEGERI DANDAMPAKNYA TERHADAP DIRI MIGRAN Suatu Tinjauan Awal terhadap Kasus Buruh Bangunan di Kuala Lumpur - M. Arif Nasution (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1998)
This writing is the outcome of studies concerning Indonesian migrant in the construction sector in Kuala Lumpur. Although in the beginning of this paper, there are many explanation about the development condition of Indonesian international labourwith the purpose to picture the global trend since the first five year development plan until the sixth five year development plan, but the focus in this writing is more on the impact analysis for the migrant one self in the destination country. The result of the studies shows that the migrant income level increase in proportion to when living in Indonesia especially infulfilling the basic requirements. On the contrary, for job experience many says that they have no progress at all and in fact rather become stupid. The migrants also infected with various diseases especially skin diseases and back ache, likewise sexual behaviour, there is a tendency to have sexual intercourse with the fellow migrant or go to the cheap prostitution places around Kuala Lumpur.